Internet of Things (IoT) Based for Landfill Gas Monitoring System - Paran, Henry; Ahmad, Afandi; Mohd Nadzri, Muhammad Muzakkir (Evolution in Electrical and Electronic Engineering, 2022)
Landfills are the most common method of waste disposal used all over the world. Gasses that are produced at the landfills can harm the workers and community. To identify the presence of harmful gasses at the landfill, an Internet of Things (IoT) based landfill gas monitoring system is suggested. The proposed solution allows for the evaluation of an application that can notify the authorities. This prototype performs in long-range data transfer by long-range wide area network (LoRaWAN) transceiver and Global System for Mobile communications (GSM), sensor node utilized the sensor gas to detect the landfill gas, Arduino Uno as a gateway equipped with GSM, LoRaWAN transceiver (transmit) and monitoring system in Favoriot IoT platform for graphical user interface (GUI) and apps. Results obtained show that the prototype able to detect four (4) types of gas such as methane, carbon dioxide, ammonia and hydrogen sulphide. Hence, it proves this prototype can be further expanded for real implementation in landfill gas research projects.